Respuesta :
Answer:
False
Step-by-step explanation:
When you multiplying powers will the same base you add the exponent, when dividing you would would subtract the exponents and when raising to a power to a power you would multiply the exponents
Answer:
False
Step-by-step explanation:
(x^3)(x^4) = (xxx)(xxxx) = x^7 when multiplying you add the exponents
(x^5)÷(x^2) = (xxxxx)÷(xx) = xxx or x^3 because two of the x's reduce therefore when dividing you subtract the exponents
(x^2)^3 = (x^2)(x^2)(x^2) = (xx)(xx)(xx) = x^6 when raising a power to a power you multiply the exponents